The individuals' initial reasons to pursue a nursing career and subsequent study dropout intentions: A cross-sectional study - Abdelmonim El Fadely; Mohamed Ait Babram; Samiha Lidrissi Hassani; Sabah Selmaoui; Boujemaa Agorram (Tehran University of Medical Sciences, 2024)
Background & Aim: Nursing staff shortages pose challenges for healthcare systems, worsened by student dropouts. This study explores the factors driving students to choose nursing to leave their programs and the relationship between reasons for choice and intentions to withdraw. Methods & Materials: A cross-sectional study was conducted at three public nursing institutes in Marrakech-Safi, Morocco. Employing a consensus sampling approach with 725 nursing students, 696 individuals responded. A researcher-made questionnaire was employed for data collection, and the data were analyzed using SPSS software (version 22). We used descriptive statistics to understand why students choose nursing and why they consider dropping out. Logistic regression was utilized to explore the correlation between reasons for selecting nursing and the intention to drop out. Results: Students primarily chose nursing to care for and help others (3.72±1.12), influenced by family/friends (3.60±1.19), and a personal interest in nursing (3.46±1.15). 28.45% of participants contemplated the idea of discontinuing their program. This inclination was mainly attributed to unfavorable clinical placements (3.59±1.21), psychological distress (3.38±1.28), and a tough curriculum (3.34±1.29). According to the predictive model, students motivated by job availability (3.587; 95% CI, 2.914-4.416; p˂.001), salary prospects (1.259; 95% CI, 1.054-1.504; p=.011), and opportunities for international work and/or study (1.196; 95% CI, 1.010-1.417; p=.038) were more likely to drop out. Conclusion: Improving clinical learning conditions, promoting a positive perception of the nursing profession, and admitting candidates driven by the aspiration to offer support and comfort to individuals appear to be pivotal in retaining students.